2000
DOI: 10.1046/j.1365-3083.2000.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cytokine Production In Vitro during the Early Phase of Birch‐Pollen Immunotherapy

Abstract: The kinetics of the immunological mechanisms during allergen-specific immunotherapy (IT) has not been thoroughly evaluated. In this investigation we study the changes in T-cell responses during the early phase of IT. Ten patients (IT group) with birch-pollen allergy were treated with conventional IT. Blood samples were collected at regular intervals for specific immunoglobulin (Ig)E measurements and preparation of peripheral blood mononuclear cells (PBMC). Seven allergic control patients (AC group) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
4
6
0
Order By: Relevance
“…The effect of grass or birch pollen immunotherapy on peripheral blood T‐cell responses to allergen remains controversial. In addition to the findings reported here, a number of other studies have reported a lack of effect of clinically successful pollen immunotherapy on peripheral blood T‐cell responses 35–37 . Our own cross‐sectional studies of peripheral blood T‐cell responses after 4–7 years of clinically effective immunotherapy 38 did not show any evidence for reduction in grass pollen‐induced proliferation or IL‐5 production 31 .…”
Section: Discussionsupporting
confidence: 64%
“…The effect of grass or birch pollen immunotherapy on peripheral blood T‐cell responses to allergen remains controversial. In addition to the findings reported here, a number of other studies have reported a lack of effect of clinically successful pollen immunotherapy on peripheral blood T‐cell responses 35–37 . Our own cross‐sectional studies of peripheral blood T‐cell responses after 4–7 years of clinically effective immunotherapy 38 did not show any evidence for reduction in grass pollen‐induced proliferation or IL‐5 production 31 .…”
Section: Discussionsupporting
confidence: 64%
“…A similar tendency was found for allergen-induced IL-18 and SLAM mRNA expression [15, 32], whereas the responses were delayed, not peaking until the end of the first treatment year, in PBMC of patients who had a less beneficial outcome. The early induction of allergen-specific IL-10 production in PBMC during SIT and sublingual immunotherapy has also been reported by other investigators, but often with no correlation with symptom improvement at later stages of SIT [31, 34, 40]. In this study, we extended the investigation of allergen-specific immune responses and their association with symptom improvement to cover the complete 3-year course of SIT.…”
Section: Discussionsupporting
confidence: 54%
“…While there is strong evidence that all these cytokines and SLAM play a role in SIT, the evidence is from short-term studies, with a maximum duration of 1 or 2 years [15, 16,29,30,31,32,33,34]. In other words, studies on these immunological mechanisms extended to cover the whole treatment period are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This is also supported by the observation that SIT-treated patients who were allergic to birch pollen experienced a significant relief in symptoms during birch pollen season; a temporary increase in allergen-specific Th2 cells was accompanied by a greater increase in Bet v 1-specific Tr1 cells. This finding may explain why the clinical improvement of patients on SIToccurs despite enhanced Th2 cytokine responses during birch pollen season (55).…”
Section: Discussionmentioning
confidence: 92%